Improving the measurement sensitivity of angular deflection of a torsion pendulum by an electrostatic spring. (19th August 2015) - Bai, Y Z; Fang, L; Luo, J; Yin, H; Zhou, Z B
Abstract: The torsion pendulum is widely employed in gravitational experiments as a weak force sensitive instrument, and its resolution is limited by the thermal noise of the pendulum and detection noise of angular deflection. Different kinds of angular deflection transducers are proposed and realized to improve its resolution. A torsion pendulum combined with an electrostatic spring is proposed here in order to improve the measurement sensitivity of angular deflection. Noise analysis and demonstration experiments show that the electrostatic torsion pendulum can relax the requirement of angular deflection detection, which is useful for gravitational experiments with much higher precision requirements.